THE USE OF ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the possibilities of applying artificial intelligence technologies in English language teaching within the context of the digital transformation of modern education. The relevance of the study is determined by the growing need to improve foreign language teaching methods, enhance the individualization of the educational process, and develop learners’ communicative competencies. The aim of the study is to analyze the pedagogical potential of artificial intelligence and determine the effectiveness of its application in English language instruction. The paper explores contemporary approaches to the use of intelligent educational technologies for developing language skills, automating assessment procedures, and organizing adaptive learning environments.The findings indicate that the integration of artificial intelligence tools contributes to increasing students’ learning motivation, promoting language autonomy, and improving reading, writing, listening, and speaking skills. At the same time, the study emphasizes the necessity of maintaining the leading role of the teacher as the organizer and facilitator of the educational process.